Tinjauan Perangkat Ajar di MAN 2 Kota Padang - Anwar Ibrahim; Nita Putri Utami (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to review the teaching tools used at Madrasah Aliyah Negeri (MAN) 2 Kota Padang in order to support the implementation of the Independent Curriculum. Observations were carried out for two months, focusing on analysis of learning documents, interviews with teachers, and direct observation of the learning process in the classroom. Observation results show that the teaching tools at MAN 2 Padang City have been prepared in accordance with the principles of the Independent Curriculum, including teaching modules, student worksheets, and formative assessments that support differentiated learning. The teachers at this madrasa show good adaptability to curriculum changes, by applying varied and contextual learning methods. Students also show a positive response to learning that is more interactive and relevant to everyday life. However, several challenges were found, such as the need for further training for teachers and the provision of more diverse learning resources. Overall, the teaching tools at MAN 2 Padang City support a more meaningful and student-centered learning process, in line with the objectives of the Independent Curriculum.